1999
DOI: 10.1300/j145v03n02_04
|View full text |Cite
|
Sign up to set email alerts
|

A Review and Reformulation of Adoptive Relationships from an Attachment Perspective

Abstract: From an attachment perspective, the formation and maintenance of adoptive relationships involve many atypical events and circumstances for both adoptive parents and adopted persons. The present analysis reviews the existing theoretical and empirical literature on several of these issues and examines the utility of conceptualizing them from an attachment perspective, focusing in particular on Bartholomew's (1990) categorical model of attachment styles. Inferences regarding the impact of attachment status (both … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 37 publications
1
8
0
Order By: Relevance
“…Further, empirical research on the characteristics of the four styles supports this assertion (e.g., Feeney et al, 1994). These findings on the attachment characteristics of the samples support Hypothesis 1 and corroborate the suggestion that attachment theory provides a useful perspective on relationship issues that arise for adoptees, including loss, search, and reunion (Edens & Cavell, 1999).…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Further, empirical research on the characteristics of the four styles supports this assertion (e.g., Feeney et al, 1994). These findings on the attachment characteristics of the samples support Hypothesis 1 and corroborate the suggestion that attachment theory provides a useful perspective on relationship issues that arise for adoptees, including loss, search, and reunion (Edens & Cavell, 1999).…”
Section: Discussionsupporting
confidence: 79%
“…Further, research in this area has lacked a strong theoretical framework. Some years ago, a theoretical paper by Edens and Cavell (1999) proposed the utility of attachment principles in the study of adoption. (Attachment refers to the affectional bond that characterizes many close relationships and that promotes a sense of comfort and security.)…”
Section: Adoption and Attachmentmentioning
confidence: 99%
“…Edens and Cavell (1999) and McGinn (2000) proposed that secure attachment with parental figures might be difficult to achieve for adoptees because previous attachment bonds would have had to be severed. Verrier (2003) suggested that this could be true even for infants adopted at birth, that attachment bonds begin prenatally and that the human foetus is already attached to the biological mother by the time of birth.…”
Section: Resultsmentioning
confidence: 99%
“…Research also has shown relations between attachment difficulties and prolonged institutional care (Tizard & Hodges, 1978) and preadoptive histories of abuse and neglect (Groze & Rosenthall, 1993). Edens and Cavell (1999) reviewed selected adoption research and reformulated the results in terms of hypotheses grounded in attachment theory. They argued that research on the role of attachment styles-secure, preoccupied, fearful, dismissive (Bartholomew, 1990)-might increase the understanding of complex processes that are unique to adoption.…”
Section: Theoretical Perspectives On Adoptionmentioning
confidence: 99%